The Administration of Escherichia coli Nissle 1917 Ameliorates Development of DSS-Induced Colitis in Mice - Rodríguez-Nogales, Alba; Algieri, Francesca; Garrido-Mesa, José; Vezza, Teresa; Utrilla, Maria P.; Chueca, Natalia; Fernández-Caballero, Jose A.; García, Federico; Rodríguez-Cabezas, Maria E.; Gálvez, Julio (Frontiers in Pharmacology, 2018)
The beneficial effects of probiotics on immune-based pathologies such as inflammatory bowel disease (IBD) have been well reported. However, their exact mechanisms have not been fully elucidated. Few studies have focused on the impact of probiotics on the composition of the colonic microbiota. The aim of the present study was to correlate the intestinal anti-inflammatory activity of the probiotic Escherichia coli Nissle 1917 in the dextran sodium sulphate (DSS) model of mouse colitis with the changes induced in colonic microbiota populations. Escherichia coli Nissle 1917 prevented the DSS-induced colonic damage, as evidenced by lower disease activity index (DAI) values and colonic weight/length ratio, when compared with untreated control mice. The beneficial effects were confirmed biochemically, since the probiotic treatment improved the colonic expression of different cytokines and proteins involved in epithelial integrity. In addition, it restored the expression of different micro-RNAs (miR-143, miR-150, miR-155, miR-223 and miR-375) involved in the inflammatory response that occurs in colitic mice. Finally, the characterization of the colonic microbiota by pyrosequencing showed that the probiotic administration was able to counteract the dysbiosis associated with the intestinal inflammatory process. This effect was evidenced by an increase in bacterial diversity in comparison with untreated colitic mice. The intestinal anti-inflammatory effects of the probiotic Escherichia coli Nissle 1917 were associated with an amelioration of the altered gut microbiome in mouse experimental colitis, especially when considering bacterial diversity, which is reduced in these intestinal conditions. Moreover, this probiotic has shown an ability to modulate expression levels of miRNAs and different mediators of the immune response involved in gut inflammation. This modulation could also be of great interest to understand the mechanism of action of this probiotic in the treatment of IBD.